IMPLICATIONS OF MARKETING DIGITALIZATION ON THE EFFECTIVENESS AND EFFICIENCY OF MARKETING COSTS IN PAMEKASAN MSMES - Rahman, Fadali; Fitriani, Syindina Anansyah; Legenda, Siti Aisyah; Firmansyah, Nur Alvian; Maulana , Irfan (Multifinance, 2025)
Based on the background of the problem, it can be seen that the objectives of this study are: 1) To determine the implications of the implementation of digital marketing on the effectiveness and efficiency of marketing costs for MSMEs in Pamekasan Regency; 2). To determine the challenges faced by MSMEs in carrying out digital marketing. In this study, researchers used a qualitative research method. The data collection technique involved conducting observations, interviews, and documentation. The data analysis used in this study was non-statistical, namely by conducting data reduction, data presentation, and data verification. The results of the study showed that: 1) The implications of the implementation of digital marketing on the effectiveness and efficiency of marketing costs for MSMEs in Pamekasan District are that it can be used as a promotional medium that does not require a lot of costs, such as printing brochures or pamphlets. In addition, it can also increase product sales volume, and can provide benefits for its business 2). The challenges faced by MSMEs in digitalizing marketing are: many competitors, lack of understanding of digital media, maintaining customer loyalty and maintaining consumer trust, and slow delivery services.